ANALISIS KINERJA REALISASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH PEMERINTAH KOTA TOMOHON TAHUN ANGGARAN 2011-2013 - Sugeha, Figih Fez; Karamoy, Herman; Pusung, Rudy J. (ACCOUNTABILITY, 2015)
Regional Government in managing the budget income and expenditure (APBD) should be realized well and properly. The performance was the image of achievement of activity inÂ  realize the objective, purpose, vision, and mission on organization. The purpose of this research is to know the performance of realized in Budget income and expenditure of the city government of Tomohon. Based on this research that had been did on Department of Revenue Finance Managing and Regional Asset (DPPKAD) City of Tomohon indicate that it performance of Income from City Government of Tomohon is good enough and can be seen from the realization of budget for the year 2011 was not accordance to the targeted, but in the next year is according on target and keep going well. But the Regional Budget Income must be enhanced by the City Government of Tomohon. Whilst the performance of expenditure was quite well because the expenditure quite relatively small and occurred saving the expenditure so that SILPA surplus can be obtain.